PENGENALAN TEKNOLOGI URBAN FARMING DENGAN METODE BUDIDAYA MICROGREEN DI SMP BAITURROSYID SCHOOL KECAMATAN KOTO TANGAH, KOTA PADANG - Roza Yunita; Jamsari Jamsari; Winda Purnama Sari; Meisilva Erona; Lily Syukriani; Firsta Ninda Rosadi; Jeanne Venora; Hasbi Al Huda (LPPM Universitas Andalas, 2023)
The concept of urban farming or urban farming is farming activities in a narrow urban environment. Urban farming is a solution to produce food independently by taking advantage of limited land in urban environments. The microgreen cultivation technique is an example of farming activities with no or narrow land, harvesting time is fast and healthy. The existence of an introduction to agriculture among adolescents can foster interest in and understanding of the concept of urban agriculture. That the concept of urban farming is not like conventional farming. It is important for us to educate young people that Indonesia has abundant natural wealth, and agriculture is one of the sectors that supports the national economy. As well as building a generation of people who love agriculture. Generations that will maintain, protect and advance the agricultural sector to meet food needs in a sustainable manner. The activity aims to introduce and practice microgreen cultivation technology to Baiturrosyid Middle School students and the surrounding community so they like to grow and consume vegetables. This activity has been carried out at the Baiturossyid School Middle School, Kec. Koto Tangah, the city of Padang. The method used is socialization, counseling, demonstration of planting microgreens in containers and discussion of microgreen cultivation techniques. The conclusion of this activity is to increase students' understanding of agriculture, students can cultivate microgreens according to the way of work that is conveyed.